Legal Protection of Women In Unregistered Inter-Citizen Marriage - Sururie, Ramdani Wahyu; Wicaksana, Dio Ashar (al-'adalah, 2019)
The phenomenon of unregistered inter-citizen marriage has been rife in several places in Indonesia. As a result of such marriages, women often have no legal power and can not obtain legal identity rights such as marriage certificates, birth certificates for their children, including material rights such as joint property and property ownership. This study examines the process of informal marriages between citizens as well as examining the extent to which the state provides legal protection to women who engage in informal marriage. The method and approach taken are normative juridical by utilizing secondary data sources in the form of legislation, books, and scientific journals. The results show that the emergence of an unregistered inter-citizen marriage is mostly due to the incompleteness of the documents needed from the country of origin of the prospective husband. To overcome this problem, the state has protected women in the form of preventive and restitutive protection women involved in intermarriages can obtain a clear legal position and protection.